Divergence in sex steroid hormone signaling between sympatric species of Japanese threespine stickleback. - Jun Kitano (Public Library of Science (PLoS), 2011)
Sex steroids mediate the expression of sexually dimorphic or sex-specific traits that are important both for mate choice within species and for behavioral isolation between species. We investigated divergence in sex steroid signaling between two sympatric species of threespine stickleback (Gasterosteus aculeatus): the Japan Sea form and the Pacific Ocean form. These sympatric forms diverge in both male display traits and female mate choice behaviors, which together contribute to asymmetric behavioral isolation in sympatry. Here, we found that plasma levels of testosterone and 17β-estradiol differed between spawning females of the two sympatric forms. Transcript levels of follicle-stimulating hormone-β (FSHβ) gene were also higher in the pituitary gland of spawning Japan Sea females than in the pituitary gland of spawning Pacific Ocean females. By contrast, none of the sex steroids examined were significantly different between nesting males of the two forms. However, combining the plasma sex steroid data with testis transcriptome data suggested that the efficiency of the conversion of testosterone into 11-ketotestosterone has likely diverged between forms. Within forms, plasma testosterone levels in males were significantly correlated with male body size, a trait important for female mate choice in the two sympatric species. These results demonstrate that substantial divergence in sex steroid signaling can occur between incipient sympatric species. We suggest that investigation of the genetic and ecological mechanisms underlying divergence in hormonal signaling between incipient sympatric species will provide a better understanding of the mechanisms of speciation in animals.